Parallel detection of SARS‐CoV‐2 epitopes reveals dynamic immunodominance profiles of CD8+ T memory cells in convalescent COVID‐19 donors. Issue 10 (14th October 2022) - van den Dijssel, Jet; Hagen, Ruth R; de Jongh, Rivka; Steenhuis, Maurice; Rispens, Theo; Geerdes, Dionne M; Mok, Juk Yee; Kragten, Angela HM; Duurland, Mariël C; Verstegen, Niels JM; van Ham, S Marieke; van Esch, Wim JE; et al.
Abstract: Objectives: High‐magnitude CD8 + T cell responses are associated with mild COVID‐19 disease; however, the underlying characteristics that define CD8 + T cell‐mediated protection are not well understood. The antigenic breadth and the immunodominance hierarchies of epitope‐specific CD8 + T cells remain largely unexplored and are essential for the development of next‐generation broad‐protective vaccines. This study identified a broad spectrum of conserved SARS‐CoV‐2 CD8 + T cell epitopes and defined their respective immunodominance and phenotypic profiles following SARS‐CoV‐2 infection. Methods: CD8 + T cells from 51 convalescent COVID‐19 donors were analysed for their ability to recognise 133 predicted and previously described SARS‐CoV‐2‐derived peptides restricted by 11 common HLA class I allotypes using heterotetramer combinatorial coding, which combined with phenotypic markers allowed in‐depth ex vivo profiling of CD8 + T cell responses at quantitative and phenotypic levels. Results: A comprehensive panel of 49 mostly conserved SARS‐CoV‐2‐specific CD8 + T cell epitopes, including five newly identified low‐magnitude epitopes, was established. We confirmed the immunodominance of HLA‐A*01:01/ORF1ab1637–1646 and B*07:02/N105–113 and identified B*35:01/N325–333 as a third epitope with immunodominant features. The magnitude of subdominant epitope responses, including A*03:01/N361–369 and A*02:01/S269–277, depended on the donors' HLA‐I context. All epitopes expressed prevalent memory phenotypes, with the highest memory frequencies in severe COVID‐19 donors. Conclusion: SARS‐CoV‐2 infection induces a predominant CD8 + T memory response directed against a broad spectrum of conserved SARS‐CoV‐2 epitopes, which likely contributes to long‐term protection against severe disease. The observed immunodominance hierarchy emphasises the importance of T cell epitopes derived from nonspike proteins to the overall protective and cross‐reactive immune response, which could aid future vaccine strategies. Abstract : Fifty‐one convalescent COVID‐19 donors were analysed for their ability to recognise 133 predicted SARS‐CoV‐2‐derived peptides restricted by 11 common HLA‐I allotypes using heterotetramer combinatorial coding. Forty‐nine mostly conserved SARS‐CoV‐2‐specific CD8 + T cell epitopes, including five new, were identified. This study revealed three dominant epitopes (HLA‐A*01:01/ORF1ab1637–1646, B*07:02/N105–113 and B*35:01/N325–333 ). The magnitude of subdominant epitope responses, including HLA‐A*03:01/N361–369 and A*02:01/S269–277, largely depended on the donors' HLA context. All epitopes had a prevalent memory phenotype, which were significantly higher in severe COVID‐19 donors.